KONSEP KESEJAHTERAAN DAlAM ISLAM (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2015)
Among the aspects that are often used as indicators of welfare measure are income, population, health, education, employment, consumption, housing, and social culture. If we use indicators will arise the question of whether the fulfillment of the indicators that a person would have to obtain welfare, why some people already have the luxury homes, vehicles, deposits and various forms of other properties should feel restless, uneasy, frightened, even there ended his life by suicide. Based on the above facts, it seems there is a lack in measuring the welfare of society. In Islamic economics, happiness is given by Allah. to anyone (male and female) who want to do good deeds along with faith in Allah. As mentioned by Allah. In Surah An-Nahl verse while the three indicators to measure welfare and happiness is a mental formation (tawhid), consumption, and the loss of all forms of fear and anxiety, as mentioned Allah. In verses 3-4 Quraish letter. As for the social concern that represented by zakat has a great potential in this country, and if it can be realized, zakat is a factor that contributes greatly to the economy of the community, especially for rural people.Di antara aspek yang sering digunakan sebagai indikator ukuran kesejahteraan adalah pendapatan, populasi, kesehatan, pendidikan, pekerjaan, konsumsi, perumahan, dan sosial budaya. Jika kita menggunakan indikator akan timbul pertanyaan apakah pemenuhan indikator bahwa seseorang harus mendapatkan kesejahteraan, mengapa beberapa orang sudah memiliki rumah mewah, kendaraan, deposito dan berbagai bentuk properti lainnya harus merasa gelisah, takut, bahkan ada yang mengakhiri hidupnya dengan bunuh diri. Berdasarkan fakta di atas, tampaknya ada yang kurang dalam mengukur kesejahteraan masyarakat. Dalam ekonomi Islam, kebahagiaan diberikan oleh Allah kepada siapapun (pria dan wanita) yang ingin melakukan perbuatan baik bersama dengan iman kepada Allah. Seperti yang disebutkan oleh Allah dalam Surat An- Nahl ayat 97, sedangkan tiga indikator untuk mengukur kesejahteraan dan kebahagiaan dalam islam adalah tauhid, konsumsi, dan hilangnya segala bentuk ketakutan dan kecemasan. hal itu seperti yang disebutkan Allah dalam ayat 3-4 surat Quraisy. Adapun kepedulian sosial yang diwakili oleh zakat memiliki potensi yang besar di negeri ini, dan jika dapat direalisasikan, zakat merupakan faktor yang memberikan kontribusi besar terhadap perekonomian masyarakat, terutama bagi masyarakat pedesaan